Relationships between docosahexaenoic acid compositions of maternal and umbilical cord erythrocytes in pregnant Japanese women. (August 2019) - Yamada, Kazumi; Kawabata, Terue; Kagawa, Yasuo; Kimura, Fumiko; Miyazawa, Teruo; Tatsuta, Nozomi; Saito, Shoji; Arima, Takahiro; Yaegashi, Nobuo; Nakai, Kunihiko
Highlights: The turning point where DHA compositions were exchanged in maternal and umbilical cord blood was 6.6%. It was observed that if DHA levels in maternal erythrocytes were greater than this turning point, DHA transfer from mother to fetus was through 'bioattenuation'. If DHA composition in maternal erythrocyte was lower than the turning point, the transfer was under 'biomagnification'. This corroborates the findings of previous research. Abstract: Previous reports have shown that the transfer of docosahexaenoic acid (DHA) from mother to fetus during pregnancy is important for development of the child's nervous and visual functions. The amount of DHA passing through the placenta varies depending on the relative DHA compositions of the erythrocytes in the maternal blood and the umbilical cord. Prior research has reported that if the DHA composition of the maternal erythrocytes is over 5.6 g%, DHA in the erythrocytes of the child undergoes bioattenuation, whereas it undergoes biomagnification if the maternal erythrocyte composition is lower than 5.6 g%. The relationship between DHA levels in maternal erythrocytes during pregnancy and in umbilical cord erythrocytes at delivery was assessed in Japanese pregnant women. This study was performed as an adjunct study of the Japan Environment and Children's Study. DHA compositions of maternal erythrocytes at 24–30 weeks of pregnancy and of umbilical cord erythrocytes at delivery were determined in 1368 mother-infant pairs. Median DHA values were 7.41% in the maternal erythrocytes and 6.84% in the umbilical cord erythrocytes, indicating significantly lower levels in the umbilical cord. When DHA composition in maternal erythrocytes was lower than 6.6%, DHA was theoretically higher in umbilical cord erythrocytes than in maternal erythrocytes. Conversely, when DHA composition in maternal erythrocytes was higher than 6.6%, DHA in umbilical cord erythrocytes was theoretically lower than in maternal erythrocytes. We therefore consider that there is a turning point of around 6% in the DHA composition of maternal and umbilical cord blood that is exchanged between mother and fetus: if the composition in the maternal blood is higher, then bioattenuation in DHA transfer from the maternal circulation to the umbilical cord occurs, while if it is lower, then biomagnification occurs. This corroborates the findings of previous research.